Parental Engagement and Academic Performance of Grade Six Pupils - Olaño, Lianna Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between parental engagement and the academic performance of Grade Six pupils in public elementary schools in District I, Schools Division Office of Antipolo City during the School Year 2025–2026. Specifically, it sought to determine the extent of parental engagement as perceived by pupils in terms of supervision and motivation, communication, class participation, and task accomplishment, and to analyze its relationship with pupils’ academic performance. The study also explored differences in perceptions when grouped according to selected demographic variables.A descriptive survey research design complemented by documentary analysis was employed. A total of 349 Grade Six pupils from Bagong Nayon I Elementary School, Dela Paz Elementary School, and Sta. Cruz Elementary School were selected using Slovin’s formula. Data were gathered through a researcher-made questionnaire-checklist, while pupils’ academic performance was based on their first and second quarter grades. Descriptive and inferential statistical tools were utilized to analyze the data.Findings revealed that parental engagement was generally high across all dimensions. Pupils demonstrated satisfactory academic performance. No significant differences were found in parental engagement when grouped according to sex, sibling position, number of children in the family, parents’ educational attainment, and father’s occupation. However, significant differences were noted in terms of monthly family income and mother’s occupation. Furthermore, a significant relationship existed between parental engagement—particularly supervision and motivation, and task accomplishment—and pupils’ academic performance, while communication and class participation showed no significant relationship.The study concluded that parental engagement significantly influences pupils’ academic performance, with certain socio-economic factors contributing to variations in engagement. It is recommended that schools strengthen home–school partnerships and implement parent-focused programs to sustain and enhance pupils’ academic success